Calculating the total value of supplier innovation. (2015) - Winter, Stefan; Lasch, Rainer; Gupta, Jatinder N.D.
Supplier innovation can contribute to a company's success, not only through cost savings, but also through revenue improvements by means of a higher chargeable price or the attraction of more customers. Although the demonstration of the measurable benefits (cost and revenue effects) from supplier innovation has been suggested in the literature, no approach to determine the total value of a supplier innovation is available. For this purpose, total cost approaches and price setting approaches were examined to design the evaluation components within our proposed total value of suppler innovation approach. We demonstrate how cost effects can be identified by total cost analysis and revenue effects by means of a conjoint analysis and a choice simulator. The developed approach and its description serve as a practical procedure to assess the monetary profitability of supplier innovation and support managers in their decision making efforts. A case example about a smart phone manufacturer demonstrates the applicability of our proposed total value of suppler innovation approach.